Initial Experience of Operator-controlled Gating Technique Under Free Breathing During CT-guided Percutaneous Drainage of Postoperative Deep Upper Abdominal Fluid Collections. Issue 9 (September 2021) - Suyama, Y.; Edo, H.; Kuwamura, H.; Enjoji, Y.; Morimura, F.; Tsuda, M.; Shinmoto, H.
Highlights: Fluid accumulated in the deep upper abdominal region is surrounded by organs. CT-guided percutaneous drainage is a feasible approach. Breathing-related body movements make percutaneous drainage difficult. Stable breath holding is also difficult for patients. Operator-controlled gating technique under free breathing is feasible and safe.